Anti-SRP immune-mediated necrotizing myopathy responsive to ofatumumab: a case report - Chen, Sihui; Yang, Jing; He, Du; Fu, Jiajia; Lai, Xiaohui; Zhao, Bi; Chen, Xueping; Shang, Huifang (Frontiers in Immunology, 2023)
Background: Immune-mediated necrotizing myopathies (IMNM) is a rare disease that was first described in 2004. Due to the lack of large case series, there are no formal treatment recommendations for IMNM.We presented a case of a 47-year-old woman who experienced progressive limb weakness, starting from the lower limbs and gradually affecting the upper limbs.She also reported experiencing dyspnea after engaging in daily activities. When she was admitted to the hospital, her upper limbs were almost unable to move and she could not stand even with support. Her Creatine kinase (CK) level significantly increased (> 3500 u/l). Electromyography showed myogenic damage, anti-Signal recognition particle (anti-SRP) and anti-Ro52 antibodies were highly positive. Pathological biopsy of the right biceps muscle showed necrotizing myopathy in the skeletal muscle. She was ultimately diagnosed with anti-SRP IMNN, and was given monotherapy with methylprednisolone and combination therapy with immunoglobulin, but her symptoms continued to worsen. The patient refused to bear the possible further liver dysfunction and blood system damage caused by Cyclophosphamide and Rituximab, and she chose to try to use Ofatumumab (OFA). Results: After receiving three doses of OFA treatment without any adverse reactions, she reported that her muscle strength had basically recovered and she was able to walk independently. The B cells in the circulatory system have been depleted, and blood markers such as liver function have consistently remained within normal range. During the follow up, her activity tolerance continued to improve.We have presented a severe case of SRP-IMNM in which the patient showed poor response to conventional immunotherapy. However, rapid symptom relief was achieved with early sequential use of OFA treatment. This provides a new option for the treatment of SRP-IMNM, and more large-scale studies will be needed in the future to verify our results.